TECHNOLOGIES OF ORGANIZATION AND MANAGEMENT OF EDUCATION AND TRAINING PROCESSES - Shokhista Akhunova; Laziz Mamajonov (Scholar Express Journals, 2022)
Organization and management of the pedagogical process in the continuing education system, implementation of tasks that serve to increase its quality and efficiency, i.e. ensuring the effectiveness of the educational process, the leaders, teachers, educators and other specialist staff of the educational institution, who are considered participants in the pedagogical process determines the need to develop and put into practice the mechanisms of coordination of activities. In the article, pedagogical processes and pedagogical systems organized in educational institutions; specific features of pedagogical processes organized in the continuous education system; issues of organization and management of the pedagogical process in the continuous education system were analyzed on a scientific basis.
Keywords: Organization and management of pedagogical processes; coordination of employees' activities; continuous education system; conflicts in the education system